Applications of Ruthenium Complexes Covalently Linked to Nucleic Acid Derivatives - Flamme, Marie (Molecules, 2018)
Oligonucleotides are biopolymers that can be easily modified at various locations. Thereby, the attachment of metal complexes to nucleic acid derivatives has emerged as a common pathway to improve the understanding of biological processes or to steer oligonucleotides towards novel applications such as electron transfer or the construction of nanomaterials. Among the different metal complexes coupled to oligonucleotides, ruthenium complexes, have been extensively studied due to their remarkable properties. The resulting DNA-ruthenium bioconjugates have already demonstrated their potency in numerous applications. Consequently, this review focuses on the recent synthetic methods developed for the preparation of ruthenium complexes covalently linked to oligonucleotides. In addition, the usefulness of such conjugates will be highlighted and their applications from nanotechnologies to therapeutic purposes will be discussed.